Responses of four citrus plants to Phytophthora-induced root rot - Tian, Li; Wu, Qiang-Sheng; Kamil Kuča,; Rahman, Mohammed Mahabubur (Penerbit Universiti Kebangsaan Malaysia, 2018)
China is one of the largest citrus producers in Asia, where Phytophthora parasitica infection has become the major threat in sustaining long term citrus production. The proposed study examined the effects of P. parasitica on Citrus junos, C. limon, C. tangerina and Poncirus trifoliata to evaluate the resisted rootstock to Phytophthora root rot. P. parasitica infection notably decreased plant growth, root morphology and activities of pathogenesis-related proteins (PRs) in C. limon and C. tangerina. Root β-1,3-glucanase, chitinase and phenylalanine ammonialyase activities significantly increased in C. junos and P. trifoliata after infection with P. parasitica. P. parasitica infection notably decreased root salicylic acid concentrations in C. limon, C. tangerina and P. trifoliata, while increasing it in C. junos. An opposite trend was observed in root jasmonic acid levels after infection with P. parasitica, relative to root salicylic acid. Root nitric oxide and calmodulin concentrations were significantly increased in P. parasitica-infected C. junos, C. tangerina and P. trifoliata, while C. limon exhibited a decrease. These results demonstrated that citrus species like C. junos and P. trifoliata displayed a much higher resistance to Phytophthora-induced root rot, and C. limon and C. tangerina showed a comparatively lower degree of resistance.